Boundary observability of wave equations with nonlinear van der Pol type boundary conditions. (December 2018) - Cai, Shuting; Xiao, Mingqing
Abstract: In this note we study the boundary observability for one-dimensional wave equation associated with nonlinear boundary condition that can generate complex dynamics. We discuss the exact observability and approximate observability, respectively, in terms of three different types of common boundary observations by studying the wave interactions on the boundary directly.